2014
DOI: 10.1002/sca.21134
|View full text |Cite
|
Sign up to set email alerts
|

SEM analysis of defects and wear on Ni–Ti rotary instruments

Abstract: SEM analysis of endodontic instruments from a Ni-Ti rotary system was assessed, before and after using them, considering their defects and deformations. Twenty Twisted File®, BioRąCe®, Mtwo®, and EndoWave® instruments were micrographed at 190× magnification. The files were washed and micrographed again to view alterations as to the presence or absence of irregular edges, grooves, microcavities, and scraping. Simulated root canal preparations were performed using these instruments. The instruments were cleaned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 21 publications
2
20
0
5
Order By: Relevance
“…As they are manufactured of M-Wire alloy, the clinical reuse of these instruments must be avoided, thereby, diminishing deterioration of the metal alloy, and consequently, the risk of an unexpected fracture of the instrument during use (3,7,9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As they are manufactured of M-Wire alloy, the clinical reuse of these instruments must be avoided, thereby, diminishing deterioration of the metal alloy, and consequently, the risk of an unexpected fracture of the instrument during use (3,7,9).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the accuracy of this method at evaluating changes in the morphological characteristics of metallic materials, such as endodontic instruments (3,7,(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in previous studies (27,28), cutting activities are reduced, and the instruments are more vulnerable to breakage. Thus, in the present study, the DR1 file was used in three samples and DR2 was used in one sample and then discarded, in accordance with the manufacturer's recommendations (29).…”
Section: Discussionmentioning
confidence: 99%